The ethics that came from the South: solidarity (Journal of Parents and Teachers, 2026)
The author of the magazine clearly outlines the mission of the NGO Justice and Peace (JP): to raise awareness of the reality of the Global South—a reality to which those in the Global North are often oblivious—in order to foster social commitment based on the value of solidarity. This reality is presented using statistical data, specifically on infant mortality rates, before moving on to the value of prophetic and personalist solidarity and its characteristics, as a means of overcoming selfishness. Finally, the proposals of some NGOs are presented from the perspective of ethics and solidarity.
Keywords: ethics; the South; solidarity; infant mortality; famine; NGOs